2017
DOI: 10.1038/s41598-017-04661-1
|View full text |Cite
|
Sign up to set email alerts
|

Danhong injection reduces vascular remodeling and up-regulates the Kallikrein-kinin system in spontaneously hypertensive rats

Abstract: Although Danhong injection (DHI) is one of the most prescribed cardiovascular medicines in China, its therapeutic indications and mechanisms remain partially defined. We now identify molecular targets of DHI in resistance vasculatures and demonstrate its role in vascular function and blood pressure (BP) regulation. BP was determined in DHI, Losartan, and placebo- treated Spontaneously Hypertensive Rats (SHR) by both noninvasive and invasive measurements. Vasorelaxation was examined both in conduit and resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…2017) [27], Losartan (positive control drug) dramatically lowered diastolic, systolic, and mean BP in SHR starting from day 1 till after 4 weeks ( *p < 0.05 vs SHR), we also found that treatment with DHI had no such immediate and aggressive effect on BP reduction in SHR as observed with Losartan, however diastolic, systolic, and mean BP were all significantly decreased compared to those of saline controls within 7 days till 4 weeks. The BP reduction effects of Danhong injection is associated in-path to the amelioration of vascular remodeling and up-regulation of the Kallikrein-kinin system.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2017) [27], Losartan (positive control drug) dramatically lowered diastolic, systolic, and mean BP in SHR starting from day 1 till after 4 weeks ( *p < 0.05 vs SHR), we also found that treatment with DHI had no such immediate and aggressive effect on BP reduction in SHR as observed with Losartan, however diastolic, systolic, and mean BP were all significantly decreased compared to those of saline controls within 7 days till 4 weeks. The BP reduction effects of Danhong injection is associated in-path to the amelioration of vascular remodeling and up-regulation of the Kallikrein-kinin system.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that DHI reversed vascular remodeling and exerted an antihypertensive effect through the Kallikrein-kinin system up-regulation in SHR [27]. In this present study, we now show that treatment with DHI/Losartan significantly reversed hypertension-induced kidney injury including renal injury biomarker KIM-1 and also provided renal-injury related genes suppression, particularly a down-regulation of renal myoglobin (Mb) gene expression confirmed by qRT-PCR and Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations